INTEGRASI DATA KEMISKINAN MENUJU CILEGON SEJAHTERA - Cipta, Hendra (Jurnal Kebijakan Pembangunan Daerah, 2025)
Poverty is a problem that occurs throughout the world, especially in developing countries such as Indonesia. With a very dense population, especially in big cities, Indonesia faces various social problems. The poverty rate in Cilegon City in the last six years has fluctuated. However, the poverty line has consistently increased from IDR 428,867 in 2018 to IDR 663,533 in 2024. In 2023, the poverty rate in Cilegon City reached 3.98%, an increase of 0.34% compared to 3.64% in 2022. However, in 2024, the poverty rate decreased slightly to 3.75%.Consolidation of Targeting Data for the Acceleration of the Elimination of Extreme Poverty (P3KE) & Integrated Social Welfare Data (DTKS) by going through a data matching process using NIK (Population Identification Number) and Name data. The process is carried out by involving the SIKS -NG Operator (Next Generation Social Welfare Information System), which then after the matching results are known, they are then processed in Microsoft Excel Working paper to facilitate analysis and updating, so that the intersection between P3KE and DTKS data will be known. In the context of P3KE (Targeting the Acceleration of the Elimination of Extreme Poverty) data, ranking refers to the grouping of households based on welfare levels.